Livelihood Transformation of Rice Farmers Amid Gold Mining Expansion: Labor Reallocation and Agricultural Sustainability in Kayuboko Village, Indonesia - Nur Avia; Lukman Najamuddin; Charles Kapil; Nuraedah Nuraedah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
Gold mining activities often generate significant socio-economic transformations within agrarian communities. This study aims to analyze changes in community livelihoods, the impact of gold mining productivity on the sustainability of rice farming, changes in farmers’ income before and after entering the mining sector, and the broader social impacts of mining activities in Kayuboko Village, West Parigi District, Parigi Moutong Regency, Central Sulawesi. A descriptive qualitative approach was employed using observation, semi-structured interviews, and documentation as data collection techniques. Research informants consisted of village officials, rice farmers, and mine workers selected purposively. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the livelihood transformation of rice farmers did not occur through a complete occupational shift but rather through an adaptive strategy involving the allocation of household time and labor between farming and mining activities. The decline in rice-field management was driven more by labor reallocation and shifting household priorities than by direct physical land degradation. Mining activities increased household income and created new economic opportunities; however, these gains were highly fluctuating and posed long-term sustainability risks. Furthermore, younger generations demonstrated a declining interest in agriculture, indicating a potential farmer succession crisis in the future. The study highlights that mining can undermine agricultural sustainability not only through ecological degradation but also through socio-economic mechanisms, including competition for household labor allocation and the erosion of social capital based on mutual cooperation